Defining energy conservation approaches by maximizing land use potential of dumpsites a study on health, safety and sustainable bio-methane powered recreational and sports complex in Camiguin Island - Ebarle, Giff dV (2011)
Camiguin as one of the prime tourist destination in the country is now enjoying the beauty of nature as its prime source of wealth and and economic stability in the entire Northern Mindanao. Despite of its limited area of land, Camiguin offers its vast natural resources that surely everyone must enjoy. But with the increasing number of population and tourist influx per year, huge problem of solid waste management is starting to surface. Based on the latest national census last 2007, the population of Camiguin Island is around more than 21,000. it is estimated to double up within a period of 10 years or less. As of current population, Camiguin generates a total of 50 tons or more of solid wastes per day. A survey conducted regarding solid waste management shows that the current disposal system in the entire island was very poor. Garbage collection system in all five municipalities within it respective political boundaries are also poor. Given that, the researcher predicts a major solid waste management problem ahead. Same scenario would be seen in the case of Boracay Island, where they are experiencing massive problems of garbage and threaten its tourism industry. If nothing major interventions will be set-up to address the issues, Camiguin might end-up to a garbage laden island in Northern Mindanao and even in the entire country. To help the Island Province formulate new approaches and techniques in handling solid waste issues, the researcher would suggest a major change in the system. The proposed set-up will start from the waste source up to proper landfill management. A major cooperation and support should be done by the stakeholders in the island to attain such change change in the system. The set-up would suggest having a landfill bioreactor as its major solution to the current issues on waste management. The landfill bioreactor is designed to handle solid waste decomposition in an environmental manner, where it minimizes all the environmental hazards posed by the conventional way of waste disposal, which is through open dumping. Aside from it, landfill bioreactor will also generates methane gas during its decomposition process, a major alternative energy source if it will be harvested properly, but also a major greenhouse gas contributor and poses health and explosion hazards if neglected. In order for the proposed set-up to work, current system of waste handling should be change. It involves segregation at source up to the collection stage, and a further segregation process in the Material Recovery Facility where non-biodegradable and biodegradable solid waste will be separated. Biodegradable waste would directly go to the landfill bioreactor for methane production and electricity generation, while the non-biodegradable waste are subjected to recycling, reuse and sell. Non-biodegradable which is not recycled, reused or no further economic value will be crushed to become a major component in making concrete hollow blocks. Concrete hollow blocks which has a mixture of crushed plastics found out to be more durable compared to the CHBs that is made up of conventional materials of sand and cement. The set-up is a long and painstakingly process in order to have a sustainable source of alternative energy and cost effective building materials. The researcher considered the process as the ultimate solution for the island's problems on solid waste management and power shortage, while ensuring health , safety and sustainable alternative source of energy.